High-toughness high-strength light-shielding polycarbonate composite material and preparation method thereof

CN120623747BActive Publication Date: 2026-10-20SUZHOU SUNWAY POLYMER
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511010853.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2026-10-20
Estimated Expiration
2045-07-22

AI Technical Summary

Technical Problem

[0004]然而,上述这类现有技术存在以下缺陷:一方面,传统的遮光填料如二氧化钛、氧化锌等在聚碳酸酯基体中易于团聚,分散性差,导致材料的力学性能下降;另一方面,为了提高遮光性能而大量添加遮光填料,往往会导致材料的韧性显著降低,刚性增加,使得材料变脆,不能满足某些需要兼顾遮光性和韧性的应用场合的需求

Benefits of technology

1、本发明选用核-壳结构的改性遮光母粒,其核心层为纳米二氧化钛与辅料的复配,低添加即可达到高遮光率;中间层采用异羟肟酸酯官能化硅烷偶联剂与聚N-乙酰葡糖胺复合改性,形成强化界面层,提高与PC基体相容性,并减少两相模量差异导致的应力突变;外层包覆超支化聚酯-弹性体共聚物,形成纳米级能量吸收网络,薄层设计不会降低整体刚性。该核-壳结构在受冲击时能吸收能量并重新分布应力,而在静态条件下保持整体刚性,解决了传统遮光填料导致的脆性问题。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a high-toughness and high-strength light-shielding polycarbonate composite material and a preparation method thereof, wherein a modified light-shielding master batch with a core-shell structure is added, the core layer is selected from at least one of nano titanium dioxide, barium silicate and nano zinc oxide; the intermediate layer is a composite interface layer formed by a hydroxamic ester functionalized silane coupling agent and poly N-acetyl glucosamine and coated on the surface of the core layer; and the outer shell layer is formed by a hyperbranched polyester-elastic copolymer coated on the outside of the intermediate layer. The material formula of the application is simple in composition, the modified light-shielding master batch with a core-shell structure is selected, the core layer raw material is low in addition, and high light-shielding rate can be achieved; the intermediate layer forms a reinforced interface layer by using a hydroxamic ester functionalized silane coupling agent and poly N-acetyl glucosamine, improves the compatibility with the PC matrix, and reduces stress mutation; the outer layer is coated with a hyperbranched polyester-elastic copolymer to form a nanoscale energy absorption network, and the balance between the mechanical properties and the light-shielding and diffuse reflection performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a high-toughness, high-strength, light-shielding polycarbonate composite material. Background Technology

[0002] Polycarbonate (PC) is a thermoplastic engineering plastic with excellent transparency, impact resistance, and dimensional stability, and is widely used in automotive, electronics, construction, and medical fields. However, pure polycarbonate materials have shortcomings in mechanical properties, light-blocking properties, and weather resistance in certain specific applications, thus requiring various modification methods to meet the application needs of different fields.

[0003] Currently, the modification of polycarbonate materials is mainly carried out through alloying and filling with inorganic materials. In terms of improving light-shielding performance, a common method is to add light-shielding fillers such as titanium dioxide and carbon black. For example, Chinese patent CN104356622A discloses a high-concentration PC reflective sheet masterbatch and its preparation method and application, comprising 30-40% PC resin, 50-60% inorganic particles, 4-10% dispersant, 1-2% flame retardant, and 1-3% light stabilizer; this technical solution improves light-shielding performance through the addition of a large number of inorganic particles.

[0004] However, the aforementioned existing technologies have the following drawbacks: on the one hand, traditional light-shielding fillers such as titanium dioxide and zinc oxide are prone to agglomeration in polycarbonate matrix, resulting in poor dispersibility and a decline in the mechanical properties of the material; on the other hand, the addition of large amounts of light-shielding fillers to improve light-shielding performance often leads to a significant decrease in the toughness and an increase in rigidity of the material, making it brittle and unable to meet the needs of certain applications that require both light-shielding and toughness.

[0005] Therefore, there is an urgent need to develop a polycarbonate composite material with a simple composition that can balance light-shielding performance and mechanical properties, so as to further broaden the application scope of PC materials in vehicles. Summary of the Invention

[0006] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a high-toughness and high-strength light-shielding polycarbonate composite material to solve the problem that it is difficult to balance mechanical properties with light-shielding and diffuse reflection properties in existing PC composite materials. At the same time, this invention will also provide a method for preparing the high-toughness and high-strength light-shielding polycarbonate composite material.

[0007] To achieve the above and other related objectives, the present invention provides the following technical solutions: A first aspect of the present invention provides a high-toughness, high-strength light-shielding polycarbonate composite material, comprising the following components in parts by weight: 80-95 parts polycarbonate; 5-20 parts of modified light-shielding masterbatch; Stabilizer 0.1-0.5 parts; Other adjuvants: 0.2-1 part.

[0008] As a preferred technical solution, the modified light-shielding masterbatch has a core-shell structure, comprising a core layer, an intermediate layer, and an outer shell layer in sequence; the core layer is selected from at least one of nano-titanium dioxide, barium silicate, and nano-zinc oxide; the intermediate layer is a composite interface layer coated on the surface of the core layer, composed of an isohydroxyoxime ester-functionalized silane coupling agent and polyN-acetylglucosamine; the outer shell layer is composed of a hyperbranched polyester-elastomer copolymer coated on the outside of the intermediate layer.

[0009] Furthermore, the core layer is a dual-light-shielding system composed of main material and auxiliary material, wherein the main material is selected from nano-titanium dioxide, and the auxiliary material is selected from barium silicate or nano-zinc oxide. Specifically, the particle size of nano-titanium dioxide is 15-30 nm, the particle size of barium silicate is 50-80 nm, and the particle size of nano-zinc oxide is 30-40 nm.

[0010] Furthermore, in the intermediate layer, isohydroxamic acid ester-functionalized silane coupling agent accounts for 1.2-3.8 wt% of the core layer mass; poly(N-acetylglucosamine) accounts for 0.4-1.2 wt% of the core layer mass. The isohydroxamic acid ester groups form a stable five-membered ring chelate structure with the metal oxide surface, and in conjunction with poly(N-acetylglucosamine), the bonding energy reaches 180-220 kJ / mol, far exceeding that of traditional silane coupling agents (80-120 kJ / mol), thus inhibiting nanoparticle aggregation. Moreover, the hydroxyl / amino groups of poly(N-acetylglucosamine) form hydrogen bonds with the ester groups of PC, creating a gradient modulus interface between the light-shielding masterbatch and the PC matrix, reducing stress abrupt changes caused by the modulus difference between the two phases.

[0011] Furthermore, the isohydroxamic acid ester functionalized silane coupling agent is preferably γ-isohydroxamic acid ester propyltrimethoxysilane (KH-560).

[0012] Furthermore, the hyperbranched polyester-elastomer copolymer has a molecular weight of 8000-12000 and a branching degree of 0.35-0.45.

[0013] Furthermore, the hyperbranched polyester-elastomer copolymer is selected from block copolymers of hydroxyl-terminated hyperbranched polyester and polyurethane elastomer.

[0014] Furthermore, the thickness of the outer shell layer is preferably 3~5 nm.

[0015] As a preferred technical solution, the modified light-shielding masterbatch is obtained by the following preparation method: (1) Mix nano-titanium dioxide with barium silicate or nano-zinc oxide in a certain proportion and perform ultrasonic dispersion treatment to obtain uniformly dispersed nano-mixed particles. (2) Dissolve isohydroxamic acid ester-functionalized silane coupling agent and poly-N-acetylglucosamine in a solvent in proportion, add nano-mixed particles to the mixed solution for reaction, and after washing, centrifugation and drying, obtain modified nano-particles coated with the intermediate layer. (3) The modified nanoparticles and hyperbranched polyester-elastomer copolymer are coated and granulated in the molten state to form a core-shell structure modified light-shielding masterbatch.

[0016] Furthermore, in step (2), the solvent is selected from at least one of water, ethanol, toluene, isopropanol, dimethyl sulfoxide, and aqueous acetic acid.

[0017] Furthermore, in step (2), the reaction temperature is 60-80℃ and the reaction time is 2-4h.

[0018] Furthermore, in step (2), after the reaction is complete, the mixture is washed three times with anhydrous ethanol, centrifuged at 8000-10000 rpm, and then vacuum dried at 80-100℃ for 6-12 hours.

[0019] Furthermore, in step (3), the temperature of melt coating granulation is 180-220℃ and the time is 10-15min.

[0020] Furthermore, in step (3), the mass ratio of the modified nanoparticles to the hyperbranched polyester-elastomer copolymer is 10:1-15:1.

[0021] As a preferred technical solution, the polycarbonate is selected from at least one of low viscosity and medium viscosity polycarbonates.

[0022] Furthermore, the polycarbonate has a melt index ranging from 1 to 50 g / 10 min and a molecular weight ranging from 20,000 to 30,000.

[0023] As a preferred technical solution, the stabilizer is a hindered phenolic compound or a mixture containing a hindered phenolic compound. Under the action of the hindered phenolic compound or mixture, the weather resistance of polycarbonate can be significantly improved, extending the long-term service life of such polycarbonate materials.

[0024] As a preferred technical solution, the other additives include at least one of antioxidants, light stabilizers, and colorants.

[0025] As a preferred technical solution, the high-toughness and high-strength light-shielding polycarbonate composite material further includes a compatibilizer, wherein the compatibilizer is selected from methyl methacrylate-butadiene-styrene copolymer, and its weight is 0.5-2 parts.

[0026] A second aspect of the present invention provides a method for preparing a high-toughness, high-strength, light-shielding polycarbonate composite material, comprising the following steps: S1. Weigh each component according to the weight ratio; S2. The weighed components are mixed in a high-speed mixer to obtain a premix; S3. Add the premixed components into the reactor, introduce supercritical CO2, stir and maintain a certain temperature and pressure for auxiliary dispersion to obtain a mixture; S4. The dispersed mixture is fed into a twin-screw extruder from the main feeder, preheated for 3-5 minutes, and then extruded and granulated to obtain the high-toughness and high-strength light-shielding polycarbonate composite material.

[0027] Furthermore, in step S2, the blending time is 10-15 min.

[0028] Furthermore, in step S3, the pressure is 20-25 MPa and the temperature is 60-65 °C.

[0029] Furthermore, in step S3, the amount of CO2 used is 3-5 wt% of the total mass of the premix.

[0030] Furthermore, in step S4, the temperature of each zone of the screw is 220℃-260℃, and the screw speed is 200-600 rpm.

[0031] As described above, the high-toughness, high-strength light-shielding polycarbonate composite material and its preparation method of the present invention have the following beneficial effects: 1. This invention uses a core-shell structured modified light-shielding masterbatch. Its core layer is a composite of nano-titanium dioxide and auxiliary materials, achieving high light-shielding efficiency with low additive levels. The middle layer is modified with isohydroxyoxime ester-functionalized silane coupling agent and poly-N-acetylglucosamine to form a reinforced interface layer, improving compatibility with the PC matrix and reducing stress abrupt changes caused by the difference in modulus between the two phases. The outer layer is coated with a hyperbranched polyester-elastomer copolymer, forming a nanoscale energy absorption network. The thin-layer design does not reduce overall rigidity. This core-shell structure can absorb energy and redistribute stress upon impact, while maintaining overall rigidity under static conditions, solving the brittleness problem caused by traditional light-shielding fillers.

[0032] 2. The material formulation provided by this invention has a relatively simple structure. While ensuring comprehensive performance advantages, it achieves a balance between mechanical properties and light-shielding and diffuse reflection properties. The entire system achieves a synergistic effect of stress dispersion and energy absorption through multi-level structural design. It has good notched impact resistance at room temperature and low temperature, with minimal reduction in rigidity, and the cost is controllable, giving it a significant competitive advantage in the market.

[0033] 3. In the process of processing, the present invention adopts a combination of supercritical CO2-assisted dispersion and high-shear twin-screw extrusion. The penetration effect of supercritical CO2 can achieve uniform dispersion of each component; and supercritical CO2 can reduce melt viscosity, promote the entanglement of poly(N-acetylglucosamine) and PC molecular chains, and improve the interfacial bonding between components.

[0034] 4. The addition of a compatibilizer in this invention helps to improve the brittleness of PC composite materials and better achieve a balance between various properties of such materials by improving their impact resistance at room temperature and low temperature.

[0035] 5. The polycarbonate composite material of this invention has a 25-30% increase in notched impact strength, while its rigidity decreases by only 3-4%, and its light-shielding rate reaches over 95%. The core-shell structure can absorb energy and redistribute stress upon impact, while maintaining overall rigidity under static conditions, thus solving the brittleness problem caused by traditional light-shielding fillers. Detailed Implementation

[0036] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.

[0037] Example 1 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material, comprising the following components in parts by weight: 90 parts polycarbonate; 10 parts modified light-shielding masterbatch; 0.3 parts stabilizer; 0.5 parts other additives; and 1 part compatibilizer.

[0038] In this high-toughness, high-strength, light-shielding polycarbonate composite material, the polycarbonate is selected from medium-viscosity polycarbonate with a melt index of 25 g / 10 min and a molecular weight of 25,000. The compatibilizer is selected from methyl methacrylate-butadiene-styrene copolymer.

[0039] The modified light-shielding masterbatch has a core-shell structure, consisting of a core layer, an intermediate layer, and an outer shell layer. The core layer is a dual-shielding system, composed of nano-titanium dioxide as the main material and barium silicate as the auxiliary material, with a mass ratio of nano-titanium dioxide to barium silicate of 3:1. The intermediate layer is a composite interface layer coated on the surface of the core layer, composed of an isohydroxyoxime-functionalized silane coupling agent and poly(N-acetylglucosamine), wherein the isohydroxyoxime-functionalized silane coupling agent accounts for 2.5 wt% of the core layer mass, and the poly(N-acetylglucosamine) accounts for 0.8 wt%. The outer shell layer is composed of a hyperbranched polyester-elastomer copolymer coated on the intermediate layer. This hyperbranched polyester-elastomer copolymer is a block copolymer of hydroxyl-terminated hyperbranched polyester and polyurethane elastomer, with a molecular weight of 10,000 and a branching degree of 0.4.

[0040] The preparation method of modified light-shielding masterbatch is as follows: (1) Core layer preparation: Nano-titanium dioxide and barium silicate are mixed at a mass ratio of 3:1, added to deionized water, and ultrasonically dispersed in an ultrasonic processor for 30 minutes to obtain a uniformly dispersed nano-mixed particle suspension. (2) Intermediate layer coating: The isohydroxamic acid ester-functionalized silane coupling agent and poly-N-acetylglucosamine were dissolved in an ethanol / water mixed solvent (volume ratio 7:3, with 1% acetic acid added) at a mass ratio of 3:1. The nano-mixed particle suspension obtained in S1 was slowly added to the mixed solution, and the reaction was stirred at 60°C for 3 hours. Then, the nanoparticles were washed with ethanol 3 times, centrifuged, and vacuum dried at 80°C for 12 hours to obtain modified nanoparticles coated with an intermediate layer. (3) Shell coating: The modified nanoparticles obtained in S2 are mixed with hyperbranched polyester-elastomer copolymer at a mass ratio of 10:1. The mixture is melt-mixed for 10 minutes in a twin-screw extruder at a temperature of 200℃ and a speed of 80rpm. After cooling and pelletizing, a core-shell structure modified light-shielding masterbatch is formed.

[0041] The preparation method of high-toughness and high-strength light-shielding polycarbonate composite material is as follows: S1. Weigh each component according to the above weight ratio; S2. Mix polycarbonate, modified light-shielding masterbatch, stabilizer, compatibilizer and other additives according to the above ratio to obtain a premix; S3. The premixed material is melt-mixed and extruded in a twin-screw extruder at a temperature of 260℃ and a speed of 100rpm. After being cooled in a cooling water tank, it is pelletized to obtain a high-toughness and high-strength light-shielding polycarbonate composite material.

[0042] Performance tests show that the high-toughness, high-strength light-blocking polycarbonate composite material prepared in this embodiment possesses excellent mechanical and light-blocking properties. Specifically, the tensile strength reaches 75 MPa, the flexural strength reaches 95 MPa, and the impact strength reaches 65 kJ / m. 2 The light transmittance is less than 0.5%. This excellent overall performance is mainly attributed to the core-shell structure design of the modified light-shielding masterbatch. The dual light-shielding system of the core layer provides excellent light-shielding performance; the isohydroxyoxime ester-functionalized silane coupling agent and poly-N-acetylglucosamine composite interface layer in the middle layer enhance the interfacial compatibility between the core layer and the outer shell layer; the hyperbranched polyester-elastomer copolymer in the outer shell layer not only improves the toughness of the material, but also improves the compatibility between the modified light-shielding masterbatch and the polycarbonate matrix.

[0043] Example 2 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. Compared with Example 1, the only difference is that the amount of modified light-shielding masterbatch is modified to 5 parts.

[0044] The high-toughness, high-strength, light-shielding polycarbonate composite material prepared in this embodiment has a light transmittance of approximately 1.2%, a tensile strength of 78 MPa, and an impact strength of 60 kJ / m². 2 .

[0045] Example 3 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. Compared with Example 1, the only difference is that the amount of modified light-shielding masterbatch is modified to 20 parts.

[0046] The high-toughness, high-strength, light-shielding polycarbonate composite material prepared in this embodiment has a light transmittance of less than 0.1%, a tensile strength of 70 MPa, and an impact strength of 68 kJ / m. 2 .

[0047] Conclusion: The test results of Examples 1-3 show that as the content of modified light-blocking masterbatch increases, the light-blocking performance and toughness of the material improve, but the tensile strength decreases slightly.

[0048] Example 4 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. Compared with Example 1, the only difference is that the isohydroxamic acid ester functionalized silane coupling agent accounts for 1.5 wt% of the core layer mass, and the poly-N-acetylglucosamine accounts for 0.5 wt% of the core layer mass.

[0049] The high-toughness, high-strength light-shielding polycarbonate composite material prepared in this embodiment has a tensile strength of 72 MPa and an impact strength of 62 kJ / m. 2 .

[0050] Example 5 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. Compared with Example 1, the only difference is that the isohydroxamic acid ester functionalized silane coupling agent accounts for 3.5 wt% of the core layer mass, and the poly-N-acetylglucosamine accounts for 1.0 wt% of the core layer mass.

[0051] The high-toughness, high-strength light-shielding polycarbonate composite material prepared in this embodiment has a tensile strength of 73 MPa and an impact strength of 67 kJ / m. 2 .

[0052] Example 6 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. Compared with Example 1, the only difference is that the molecular weight of the hyperbranched polyester-elastomer copolymer is 8500 and the degree of branching is 0.38.

[0053] The high-toughness, high-strength light-shielding polycarbonate composite material prepared in this embodiment has a tensile strength of 74 MPa and an impact strength of 63 kJ / m. 2 .

[0054] Example 7 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. The only difference from Example 1 is that the molecular weight of the hyperbranched polyester-elastomer copolymer is 11,500 and the degree of branching is 0.43.

[0055] The high-toughness, high-strength light-shielding polycarbonate composite material prepared in this embodiment has a tensile strength of 72 MPa and an impact strength of 66 kJ / m. 2 .

[0056] Example 8 This embodiment provides a method for preparing a high-toughness and high-strength light-shielding polycarbonate composite material. The method uses supercritical CO2-assisted dispersion technology to improve the dispersion uniformity and performance of the composite material.

[0057] The preparation method specifically includes the following steps: S1. According to the component ratio of the high-toughness and high-strength light-shielding polycarbonate composite material described in Example 1, weigh out 90 parts of polycarbonate, 10 parts of modified light-shielding masterbatch, 0.3 parts of stabilizer, 0.5 parts of other additives, and 1 part of compatibilizer. The types of polycarbonate, modified light-shielding masterbatch, stabilizer, compatibilizer, and other additives are the same as in Example 1.

[0058] S2. Add the components weighed in S1 into a high-speed mixer and mix at 1500 rpm for 5 minutes to make the components initially mixed evenly, and obtain a premix.

[0059] S3. Add the premix obtained in S2 to a high-pressure reactor, seal the reactor and introduce supercritical CO2, the amount of CO2 being 4wt% of the total mass of the premix; under the conditions of pressure of 22MPa and temperature of 63℃, stir at 200rpm for 30 minutes to allow the supercritical CO2 to fully penetrate into the premix and assist in dispersing the modified light-shielding masterbatch, thus obtaining the mixture.

[0060] S4. The dispersed mixture is fed into a twin-screw extruder from the main feedstock, preheated for 4 minutes, and then extruded and granulated to obtain a high-toughness, high-strength, light-shielding polycarbonate composite material. The mixture obtained from S3 is fed into a twin-screw extruder through the main feed port, preheated at 260°C for 4 minutes, and then extruded at a screw speed of 100 rpm. After cooling in a water tank, it is pelletized to obtain a high-toughness, high-strength, light-shielding polycarbonate composite material.

[0061] Performance tests show that the high-toughness and high-strength light-shielding polycarbonate composite material obtained by the preparation method in this embodiment has an increased tensile strength of approximately 5% compared to Example 1, reaching 78.5 MPa; and an increased impact strength of approximately 8%, reaching 70 kJ / m.2 The light transmittance was reduced to below 0.3%. This is mainly attributed to the application of supercritical CO2-assisted dispersion technology. Supercritical CO2 can penetrate into the polymer matrix, reduce the viscosity of the system, promote the uniform dispersion of modified light-shielding masterbatch in the polycarbonate matrix, reduce agglomeration, and thus improve the overall performance of the material.

[0062] Example 9 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. Compared with Example 8, the only difference is that the amount of modified light-shielding masterbatch is modified to 5 parts.

[0063] The high-toughness, high-strength light-shielding polycarbonate composite material prepared in this embodiment has a tensile strength of 81 MPa and an impact strength of 65 kJ / m. 2 The light transmittance is approximately 0.9%.

[0064] Example 10 This embodiment provides a high-toughness and high-strength light-shielding polycarbonate composite material. Compared with Example 8, the only difference is that the amount of modified light-shielding masterbatch is modified to 20 parts.

[0065] The high-toughness, high-strength light-shielding polycarbonate composite material prepared in this embodiment has a tensile strength of 74 MPa and an impact strength of 73 kJ / m. 2 The light transmittance is less than 0.08%.

[0066] In summary, the material formulation of this invention is simple, employing a core-shell structured modified light-shielding masterbatch, achieving high light-shielding efficiency with low addition of core layer raw materials; the intermediate layer utilizes isohydroxamic acid ester-functionalized silane coupling agent and poly-N-acetylglucosamine to form a reinforced interface layer, improving compatibility with the PC matrix and reducing stress abrupt changes; the outer layer is coated with a hyperbranched polyester-elastomer copolymer, forming a nanoscale energy absorption network, achieving a balance between mechanical properties and light-shielding and diffuse reflection properties. Therefore, this invention effectively overcomes the various shortcomings of existing technologies and possesses high industrial application value.

[0067] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A high-toughness, high-strength, light-shielding polycarbonate composite material, characterized in that, The components include the following parts by weight: 80-95 parts polycarbonate; 5-20 parts of modified light-shielding masterbatch; Stabilizer 0.1-0.5 parts; Other auxiliary agents: 0.2-1 part; The modified light-shielding masterbatch has a core-shell structure, comprising a core layer, an intermediate layer, and an outer shell layer. The core layer is selected from at least one of nano-titanium dioxide, barium silicate, and nano-zinc oxide. The intermediate layer is a composite interface layer coated on the surface of the core layer, consisting of an isohydroxyoxime ester-functionalized silane coupling agent and poly(N-acetylglucosamine). The outer shell layer is composed of a hyperbranched polyester-elastomer copolymer coated on the outside of the intermediate layer. The core layer is a double light-shielding system composed of main material and auxiliary material, wherein the main material is selected from nano titanium dioxide and the auxiliary material is selected from barium silicate or nano zinc oxide. In the intermediate layer, isohydroxamic acid ester-functionalized silane coupling agent accounts for 1.2-3.8 wt% of the core layer mass, and poly-N-acetylglucosamine accounts for 0.4-1.2 wt% of the core layer mass; The hyperbranched polyester-elastomer copolymer is selected from block copolymers of hydroxyl-terminated hyperbranched polyester and polyurethane elastomer.

2. The high-toughness, high-strength, light-shielding polycarbonate composite material according to claim 1, characterized in that, The hyperbranched polyester-elastomer copolymer has a molecular weight of 8000-12000 and a branching degree of 0.35-0.

45.

3. The high-toughness, high-strength, light-shielding polycarbonate composite material according to claim 1 or 2, characterized in that, The modified light-shielding masterbatch is obtained by the following preparation method: (1) Mix nano-titanium dioxide with barium silicate or nano-zinc oxide in a certain proportion and perform ultrasonic dispersion treatment to obtain uniformly dispersed nano-mixed particles. (2) Dissolve isohydroxamic acid ester-functionalized silane coupling agent and poly-N-acetylglucosamine in a solvent in proportion, add nano-mixed particles to the mixed solution for reaction, and after washing, centrifugation and drying, obtain modified nano-particles coated with the intermediate layer. (3) The modified nanoparticles and hyperbranched polyester-elastomer copolymer are coated and granulated in the molten state to form a core-shell structure modified light-shielding masterbatch.

4. The high-toughness, high-strength, light-shielding polycarbonate composite material according to claim 1, characterized in that, The polycarbonate is selected from at least one of low viscosity and medium viscosity polycarbonates; the polycarbonate has a melt index range of 1-50 g / 10 min and a molecular weight range of 20,000-30,000.

5. The high-toughness, high-strength, light-shielding polycarbonate composite material according to claim 1, characterized in that, The high-toughness and high-strength light-shielding polycarbonate composite material further includes a compatibilizer, which is selected from methyl methacrylate-butadiene-styrene copolymer, and its weight is 0.5-2 parts.

6. A method for preparing a high-toughness, high-strength, light-shielding polycarbonate composite material as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Weigh each component according to the weight ratio; S2. The weighed components are mixed in a high-speed mixer to obtain a premix; S3. Add the premixed components into the reactor, introduce supercritical CO2, stir and maintain a certain temperature and pressure for auxiliary dispersion to obtain a mixture; S4. The dispersed mixture is fed into a twin-screw extruder from the main feeder, preheated for 3-5 minutes, and then extruded and granulated to obtain the high-toughness and high-strength light-shielding polycarbonate composite material.

7. The preparation method according to claim 6, characterized in that, In step S3, the pressure is 20-25 MPa, the temperature is 60-65℃, and the amount of CO2 used is 3-5 wt% of the total mass of the premix.

Citation Information

Patent Citations

  • High-concentration PC reflector plate master batch and preparation method and application thereof

    CN104356622A

  • Hyperbranched aqueous polyurethane nano zinc oxide composite material and preparation method thereof

    CN109021550A

  • Polyurethane film high-concentration high-dispersion ultraviolet-shielding shading master batch and preparation method thereof

    CN118185290A